2017
DOI: 10.1021/acs.biochem.7b00238
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Heterogeneity and the Affinity of Substrate Molecular Recognition by Cytochrome P450cam

Abstract: The broad and variable substrate specificity of cytochrome P450 enzymes makes them a model system for studying the determinants of protein molecular recognition. The archetypal cytochrome P450cam (P450cam) is a relatively specific P450, a feature once attributed to the high rigidity of its active site. However, increasingly studies have provided evidence of the importance of conformational changes to P450cam activity. Here we used infrared (IR) spectroscopy to investigate the molecular recognition of P450cam. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…Therefore, as quantified in the current work, the dynamics of B' helix also plays an important role in defining the conformational heterogeneity in cytochrome p450. Together, the present work provides a quantitative perspective to the notion of conformational heterogeneity in substrate-free P450cam, previously proposed by multiple spectroscopic investigations [19][20][21]. The current work's prediction of a dynamic equilibrium between closed and open conformation of substrate-free P450cam, with the equilibrium tilted towards closed conformation, suggest an interesting functional implication related to substrate-recognition process in cytochrome P450cam: while substrate like camphor would visit both open and closed conformations of P450cam, it would mostly encounter the closed conformation due to its significantly…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, as quantified in the current work, the dynamics of B' helix also plays an important role in defining the conformational heterogeneity in cytochrome p450. Together, the present work provides a quantitative perspective to the notion of conformational heterogeneity in substrate-free P450cam, previously proposed by multiple spectroscopic investigations [19][20][21]. The current work's prediction of a dynamic equilibrium between closed and open conformation of substrate-free P450cam, with the equilibrium tilted towards closed conformation, suggest an interesting functional implication related to substrate-recognition process in cytochrome P450cam: while substrate like camphor would visit both open and closed conformations of P450cam, it would mostly encounter the closed conformation due to its significantly…”
supporting
confidence: 57%
“…The presence of a mobile active site and speculation of conformational selection based substrate binding mechanism have been supported by Infrared spectroscopic investigations. 21 Conformational fluctuation is known to play key role in substrate recognition across multiple P450s, but only recently have specific details about the conformational space sampled by a given enzyme are emerging. 12,[22][23][24] Together, these findings have introduced the notion of complex 'conformational heterogeneity' in the substrate-free P450cam and its role in modulating substrate recognition by P450cam is slowly being appreciated.…”
mentioning
confidence: 99%
“…The Y96F mutant of CYP101D2, where the hydrogen bond interaction is again missing, catalyzed (1R)‐camphor to (1R)‐5‐ exo ‐hydroxycamphor with 92% yield, again showing that interaction between the substrate and Y96 is less critical than the hydrophobic interactions . Basom et al showed that dynamics of the population state of the conformations oriented in the correct regioselectivity was not significantly affected by Y96 mutation, hence they also suggested that this hydrogen bond is less significant than was previously proposed …”
Section: Resultsmentioning
confidence: 92%
“…88 Basom et al showed that dynamics of the population state of the conformations oriented in the correct regioselectivity was not significantly affected by Y96 mutation, hence they also suggested that this hydrogen bond is less significant than was previously proposed. 89,90 In the crystal structure, where camphor is bonded to Y96, the critical bond between the distal oxygen on heme (O d ) and the carbon to be oxidized on camphor is 3.6 Å. This carbon is the closest one to O d .…”
Section: Electronic Features Of the Active Sitementioning
confidence: 99%
“…13,14 It has recently been demonstrated that the presence of an infrared label at the site of recognition between a protein and its binding partner can give site specific insight into the underlying mechanisms of how signaling proteins function. [15][16][17][18][19] Such studies require a special vibrational label that absorbs in the spectral window between ≈1700 cm −1 to ≈2800 cm −1 in order to discriminate it from a huge protein background. [20][21][22][23][24][25] Among the possible molecular groups that have been proposed in that regard, 16,17,19,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] we favor the noncanonical amino acid azidohomoalanine (Aha).…”
Section: Introductionmentioning
confidence: 99%